Strengthening the Role of Insurance Companies in the Financial Market in The Republic of Uzbekistan (Eurasian Journal of History, Geography and Economics, 2022)
This article examines the content of the insurance mechanism, the role and importance of the country’s economy in the development of the country, the views of economists on increasing the role of the insurance industry in the financial market. At the same time, the financial analysis of insurance companies operating in the Republic of Uzbekistan, as well as foreign experience based on the position of the insurance market of foreign countries in the field of portfolio investment. Scientific conclusions and proposals have been formed to increase the position of insurance companies in the financial market of the country